Устойчивость безмоментной цилиндрической оболочки-мембраны в сверхзвуковом потоке газа - Л. А. Ванян (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The stability of momentless cylindrical membrane shell in the two-dimensional flow of gas is investigated here. The areas of instability are compared according to “piston” theory and the one of precise approximation, when the aerodynamical pressure dependence from the motion of membrane has non-local character of differential type. Unlike the “piston” theory, the calculations according to the theory of precise approximation show the instability of membrane under the small supersonic numbers of Mach. At the same time the upper verge (border) of stability area is considerably reduced as well.
Keywords: Mechanics of deformable solids; Thin bodies, structures